Wiley practitioner's guide to GAAP 2022 : interpretation and application of generally accepted accounting principles - Flood, Joanne M. (Wiley Regulatory Reporting Ser., 2022)
"Wiley GAAP 2020: Interpretation and Application of Generally Accepted Accounting Principles is a thorough study and analysis of all US Generally Accepted Accounting Principles (GAAP) set forth in the pronouncements of the FASB (Financial Accounting Standards Board) and its predecessors. This useful guide also contains AICPA Accounting Standards Executive Committee (ASEC) Statements of position. All pronouncements are explained with relevant terminology and practice-oriented real world examples. Each chapter is composed of a discussion of perspectives and issues, sources of GAAP, a definition of terms, concepts, rules and examples, and, where applicable, specific appendices"--